2001
DOI: 10.1152/jn.2001.86.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Models of Respiratory Rhythm Generation in the Pre-Bötzinger Complex. III. Experimental Tests of Model Predictions

Abstract: We used the testable predictions of mathematical models proposed by Butera et al. to evaluate cellular, synaptic, and population-level components of the hypothesis that respiratory rhythm in mammals is generated in vitro in the pre-Bötzinger complex (pre-BötC) by a heterogeneous population of pacemaker neurons coupled by fast excitatory synapses. We prepared thin brain stem slices from neonatal rats that capture the pre-BötC and maintain inspiratory-related motor activity in vitro. We recorded pacemaker neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
186
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(214 citation statements)
references
References 33 publications
24
186
4
Order By: Relevance
“…This excitatory waveform originates in the pre-BötC (Butera et al 1999b;Del Negro et al, 2001) and propagates, according to our data, with high fidelity. Despite marked differences in preMN and MN size/somatodendritic morphology, synaptic conductance/current densities are similar.…”
Section: Synaptic Drive Waveforms Premn/mn Spiking Patterns and Fidsupporting
confidence: 73%
See 1 more Smart Citation
“…This excitatory waveform originates in the pre-BötC (Butera et al 1999b;Del Negro et al, 2001) and propagates, according to our data, with high fidelity. Despite marked differences in preMN and MN size/somatodendritic morphology, synaptic conductance/current densities are similar.…”
Section: Synaptic Drive Waveforms Premn/mn Spiking Patterns and Fidsupporting
confidence: 73%
“…To accomplish this, we exploited neonatal rat medullary slice preparations, which are used for analysis of inspiratory rhythm and pattern generation mechanisms (Smith et al, 1991;Koshiya and Smith, 1999;Del Negro et al, 2001). These slices contain active rhythm-generating pre-BötC neurons and circuits transmitting rhythmic inspiratory drive to XII MNs.…”
Section: Introductionmentioning
confidence: 99%
“…Transection along the midline severs axonal connections between the bilateral pre-Bötzinger complex nuclei that lie dorsal to the midline raphe nuclei. Therefore, fibers of passage between pre-Bötzinger complex nuclei may play a role in coordinating rhythmic output (6). However, this alternative is not supported by our findings that transient, strong stimulation of raphe neurons by IA eliminated the altered breathing periods (Fig.…”
Section: Disruption Of Respiratory Rhythm: Interpretation Of Altered contrasting
confidence: 58%
“…Alternatively, the microtubule may have destroyed fibers of passage between the bilaterally located pre-Bötzinger complex neurons. This alternative is suggested by findings that perturbations in respiratory rhythm occur after midline transection of medullary slices in solution (6). Transection along the midline severs axonal connections between the bilateral pre-Bötzinger complex nuclei that lie dorsal to the midline raphe nuclei.…”
Section: Disruption Of Respiratory Rhythm: Interpretation Of Altered mentioning
confidence: 99%
“…It has been suggested that I NaP plays an essential role in the activation of pacemaker neurons in the pre-Bötzinger Complex (pBC), a region within the rostroventrolateral medulla (RVLM), in vitro (Butera et al 1999;Del Negro et al 2001;Smith et al 2000). Del Negro et al (2002) experimentally characterized I NaP in pBC neurons.…”
Section: Introductionmentioning
confidence: 99%